Synthesis And Charaterization Of Mesoporous SBA-15 A Material Evaluation For Roles In Catalysis. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2005)
Mesoporous molecular sieve is a new class of materials that shows high potential in various applications, particularly catalysis.